098 The prevalence of progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) in Scotland. Issue 9 (12th August 2022) - Swallow, Diane; Counsell, Carl
Abstract : Background and Objectives: We estimated the point prevalence of progressive supranuclear palsy (PSP) and corticobasal syndrome (CBS) at regional and national levels in Scotland, UK as there are few high- quality prevalence studies of these conditions. Methods: Nationally, multiple methods of case ascertainment were used including clinician and nurse specialist referral, searches of ICD-10 diagnostic coding in routinely collected electronic health data (Scottish Morbidity Record), and patient self-referral. In one region we also searched GP databases and unselected hospital correspondence. Cases were verified by clinical examination or medical record review. National and regional total and age-sex stratified crude prevalence rates on 31st December 2018 were calculated. Results: The regional crude point prevalence was 4.28 per 100, 000 (95% CI 2.90, 6.31) for PSP, and 2.05 per 100, 000 (95% CI 1.17, 3.59) for CBS. The national crude prevalence rates were lower due to the greater reliance on passive case ascertainment. There were no clear sex differences in the prevalence rates and peak prevalence was in the 70-79 age-group. Discussion: The prevalence rates of PSP and CBS were similar to previous estimates with little change over the past 20 years.